Prediction of physical body composition and carcass components from live-weight and body measurements in Ethiopian highland Zebu (Bos indicus) oxen - Wolde Michael, T.; Yimegnuhal, A.; Osuji, P.O.; Diedhiou, M.L. (Ethiopian Society of Animal Production, 2004)
Body measurements and slaughter weight of body component (carcass and edible non-carcass) of 63 zebu oxen were used in this trial. Out of these 9 of them were slaughtered at the initial stage of the experiment. The remaining 54 oxen were allocated to various levels of feeding or plane of nutrition. From this group 24 of them were subjected to work for 24 days. Empty body weight (EBW) was calculated by subtracting the weight of gut content from slaughter weight. The coefficient of correlation on slaughter with empty body weight and hot carcass weight were 0.98 and 0.96 respectively. The regression of body components (empty body weight, carcass weight, lean, fat, bone, hump, external and internal offal) on slaughter weight gave better relationship than the rest of the body parts. The weights of body composition of one livestock unit (LU=250 kg live weight) using derived equation from live weight indicated that empty body weight was 86% while hot carcass was 51% of body weight. It was observed that the coefficient correlation of slaughter weight, empty body weight, hot carcass weight, external offal and internal offal were well above 0.70. Body components were moderately correlated with measured wither height, height and width of hump and body sheath. Their relationship ranged from 0.62 to 0.70. Bone, fat and hump were poorly related with body length. Moreover, the equation Y (Mean weight) = 1.0223 plus minus 0.6950*x (body length) + 0.0109x square plus minus 0.0056 had a coefficient of determination (R square ) of 99.24% provided simple and better measuring device to estimate body weight of Zebu cattle from body length. The relationship may assist to develop simple guideline to estimate live weight in places where there are no appropriate measuring devices.